Perlindungan Hukum bagi Pemegang Hak Cipta dan Penerapan Asas Ittikad Baik dalam Cover Lagu untuk Tujuan Komersil di Youtube - Habibi, Miftakhur Rokhman (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2024)
Rampant copyright infringement often occurs and is usually found on social media such as YouTube, where many songs are covered without permission from the original owner of the song. This is considered very detrimental to the owner of the original song as the holder of exclusive copyright rights, including his economic rights. The results of this study indicate that legal protection for copyright holders has been sufficiently regulated in Law Number 28 of 2014 concerning Copyright, where the Copyright Owner has exclusive rights consisting of Moral Rights and Economic Rights. If there is a violation of copyright on his work, he can take civil law action by filing a lawsuit with the Commercial Court, as well as criminal charges based on Article 113 of the Copyright Law. The application of the principle of good faith in song covers for commercial purposes on YouTube is still lacking from the song cover party as the content creator, where it was found that the singer of the song cover did not have direct permission from the creator but had dared to collaborate with YouTube as the owner of the platform.